A digital workflow with the virtual enamel evaluation and stereolithographic template for accurate tooth preparation to conservatively manage a case of complex exogenous dental erosion. Issue 5 (30th October 2021) - Luo, Tian; Zhang, Junjing; Fan, Lin; Huang, Yutian; Yu, Jiayi; Yu, Haiyang
Abstract: Objective: This article describes a digital workflow using virtual enamel evaluation and a stereolithographic template for accurate tooth preparation for a complex exogenous dental erosion. Clinical Considerations: A 22‐year‐old man with different degrees of defects on the labial surface in esthetic area was diagnosed as exogenous dental erosion. The residual undamaged enamel area and depth of defect were measured and analyzed accurately by creating a digital virtual patient based on the pretreatment data. According to the different conditions of residual enamel and tooth defect, the treatment plans of porcelain veneer, crown and composite resin were chosen for corresponding involved teeth. Based on the virtual wax‐up and the suggested material thickness, a template for tooth preparation was designed and three‐dimensional printed. This template together with a special bur indicating the reduction depth accurately guided the teeth preparation and achieved a long‐term effect. Conclusions: The virtual enamel evaluation contributes to obtaining the appropriate corresponding treatment plan objectively. The stereolithographic template effectively meets the accuracy of tooth preparation, preserving the tooth hard tissue to the greatest extent. Clinical Significance: The digital workflow described here may provide a quantifiable evaluation method and an accurate tooth preparation method for exogenous dental erosion.